Tailoring Noble Metal-Free Ti@TiO2 Photocatalyst for Boosting Photothermal Hydrogen Production - El Hakim, Sara; Chave, Tony; Nada, Amr A.; Roualdes, Stéphanie; Nikitenko, Sergey I. (Frontiers in Catalysis, 2021)
In this work, we provide new insights into the design of Ti@TiO2 photocatalyst with enhanced photothermal activity in the process of glycerol reforming. Ti@TiO2 nanoparticles have been obtained by sonohydrothermal treatment of titanium metal nanoparticles in pure water. Variation of sonohydrothermal temperature allows controlling nanocrystalline TiO2 shell on Ti0 surface. At 100 < T < 150°C formation of TiO2 NPs occurs mostly by crystallization of Ti(IV) amorphous species and oxidation of titanium suboxide Ti3O presented at the surface of Ti0 nanoparticles. At T > 150°C, TiO2 is also formed by oxidation of Ti0 with overheated water. Kinetic study highlights the importance of TiO2 nanocrystalline shell for H2 generation. Electrochemical impedance spectroscopy points out more efficient electron transfer for Ti@TiO2 nanoparticles in correlation with photocatalytic data. The apparent activation energy, Ea = (25–31) ± 5 kJ·mol−1, assumes that photothermal effect arises from diffusion of glycerol oxidation intermediates or from water dynamics at the surface of catalyst. Under the heating, photocatalytic H2 emission is observed even in pure water.